Does the Timing of the Initiation of Physical Therapy Post‐Rotator Cuff Repair Impact Shoulder Function? - Reivian Berrios Barillas; James Irrgang (Health Care Science, 2025)
ABSTRACT Background Rehabilitation typically restores shoulder function after a common rotator cuff repair; however, it is unclear when to initiate physical therapy (PT) post‐surgery. To understand effective start times, this study analyzed PT start times and their effect on shoulder function. The most effective shoulder outcomes were hypothesized to occur when PT started 0–4 weeks post‐surgery. Methods Data from 1002 patients who underwent rotator cuff repair were analyzed retrospectively from 52 outpatient clinics in the years of 2016–2021. The primary data of timings between surgery and the start of PT (0–2 weeks [0–14 days], 2–4 weeks [15–28 days], 4–6 weeks [29–42 days], and 6–14 weeks [43–100 days]), change in functional shoulder scores, number of PT visits utilized, and functional scores changed per visit were analyzed. Regression analyses of the impact of age, sex, payor source, and tear size were completed. Results The change in functional scores and functional scores changed per visit are not affected by the initiation timing of PT post‐ rotator cuff surgery, when controlling for baseline functional scores. This result is revealed despite initial functional scores being significantly different. Functional scores change per visit may have been affected by payor source (R2 = 0.004, p ≤ 0.010). PT start times may have been impacted by age (R2 = 0.010, p = 0.007), payor source (R2 = 0.016, p = 0.001), and tear size (R2 = 0.007, p = 0.026). Payor source may have influenced the number of PT visits (R2 = 0.060, p < 0.001). Conclusions After rotator cuff surgery, patients should choose to complete rehabilitation to optimize shoulder function. However, the initiation timing of PT may not affect functional shoulder outcomes.